Informality features in Thai EFL academic writing: Corpus evidence and instructor perceptions - Suwannasom, Thitirat (Universitas Ahmad Dahlan, 2025)
In recent years, a slight increase in the use of informal elements has been observed in academic writing, indicating a shift toward a more interactive connection between authors and readers in scholarly communication. Although more flexibility is found in academic texts, EFL students’ ability to develop academic writing styles has not been fullyexplored in the Thai context. This research investigated the distribution of 10 informal features established by Hyland and Jiang (2017) in Thai EFL students’ academic essays and examined EFL writing instructors' perceptions of such features. The data were collected from a corpus of 147 academic essays (63,029 words) written by Thai undergraduate English majors. The survey responses were obtained from 31 EFL writing instructors regarding their perceptions of informal features collected through online questionnaire responses. The results revealed that the most frequently occurring informal features were second-person pronouns, first-person pronouns, and sentence-initial conjunctions, respectively. While the writing instructors perceived split infinitives, unattended anaphoric pronouns, and sentence-final prepositions as highly acceptable informal features, they were unlikely to approve of contractions, sentence-initial conjunctions, and exclamations in students’ academic assignments. The study combines corpus-based evidence with instructor perspectives to reveal a mismatch between students’ linguistic practices and academic writing expectations in the Thai context. It further suggests that explicit instruction in academic writing conventions should be more fully integrated into the writing curriculum to strengthen EFL students’ understanding and development of academic discourse proficiency.